Implementasi Seed Phrase Dalam Keamanan Dompet Kripto Pada Metamask - Fernanda Kalvin; Muhammad Ibnu Sa'ad; Ahmad Fahrijal Pukeng (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Seed phrases are a crucial element in the security system of non-custodial crypto wallets like MetaMask. These phrases allow users to recover their wallets and serve as the primary key to access digital assets. This research aims to analyze and implement seed phrase-based security in crypto wallets, using MetaMask as a case study. Through literature review and technical simulation, this study explains how seed phrases function, the potential risks if compromised, and possible mitigation strategies. The results show that while seed phrases are vital for maintaining user asset security and integrity, they can be a vulnerability if not properly protected.